Influence of the Dry Yeast Preparation Method on Final Sparkling Wine Characteristics - Carmen Berbegal; Lucía Polo; M. José García-Esparza; Inmaculada Álvarez; Fernando Zamora; Sergi Ferrer; Isabel Pardo (Fermentation, 2022)
The effect of preparing the commercial yeast prise de mousse S. cerevisiae IOC 18-2007 on the second fermentation kinetics of a Macabeo white base wine was evaluated. The influence of yeast preparation on the final “Cava” sparkling wines was determined. The medium glucose, peptone, yeast extract (GPY medium), and the characteristic classic pied de cuve procedure were used to prepare the inoculum, which was placed besides a tirage liqueur inside bottles in which a second fermentation took place by the “traditional method”. The fermentation kinetics were similar for the first 60 days regardless of the employed yeast inoculum preparation. In both cases, glucose was exhausted and a few grams of fructose remained on day 30. The ethanol concentration after 60 days was the same in all of the wines. The sparkling wines inoculated with the GPY-grown yeasts showed higher titratable acidity, lower total polysaccharide and protein contents, and greater foamability (HM) and foam stability (HS). Regarding volatile compounds, these wines contained higher esters, fatty acids, higher alcohols, and γ-butyrolactone. Differences in the wine’s visual and flavor attributes were not significant no matter what inoculum was used. However, the aroma score was significantly higher in the wines inoculated with the pied de cuve-prepared yeasts.